2013
DOI: 10.1144/qjegh2011-028
|View full text |Cite
|
Sign up to set email alerts
|

Rapid observations to guide the design of systems for long-term monitoring of a complex landslide in the Upper Lias clays of North Yorkshire, UK

Abstract: The Whitby Mudstone Formation has one of the highest landslide densities in the UK with 42 landslides per 100 km 2 . Landsliding at Hollin Hill in North Yorkshire, UK is complex and continuing, and includes shallow, retrogressive rotational failure on the upper slope, translation, and flow from the base of the Whitby Mudstone Formation over the scarp slope of the Staithes Sandstone Formation. Surface observations augmented by information relating to lithological, moisture and strength v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 14 publications
2
26
0
Order By: Relevance
“…This is supported by Gunn et al . (), who reported water and washed out fine material emerging from the slip surfaces at the earthflow toes during periods of activation. Likewise this is also consistent with observations on other slow moving landslide where the role of fissuring, including the dynamic opening and closing of flow pathways, is seen to significantly influence ground water movement (Van Asch et al ., ; Bièvre et al, ; Krzeminska et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by Gunn et al . (), who reported water and washed out fine material emerging from the slip surfaces at the earthflow toes during periods of activation. Likewise this is also consistent with observations on other slow moving landslide where the role of fissuring, including the dynamic opening and closing of flow pathways, is seen to significantly influence ground water movement (Van Asch et al ., ; Bièvre et al, ; Krzeminska et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…The site has been monitored since 2009 by the British Geological Survey (BGS) using various methods, including terrestrial and airborne laser scanning, as well as ground-based geotechnical and geophysical investigations. BGS investigations have revealed that the landslide has a complex behaviour with seasonal surface variations and episodic failures mostly triggered by intensive rainfall and increased pore-water pressures within the constituent geological materials (Gunn et al, 2013;Uhlemann et al, 2017).…”
Section: Study Areamentioning
confidence: 99%
“…Monitoring of these structures can provide a valuable insight into a landslide's subsurface dynamic failure mechanism and thereby help mitigate hazards (Gunn et al, 2013). Conventionally, in addition to geotechnical and geophysical monitoring of the subsurface, survey markers are often used to quantify surface displacement by monitoring discrete locations through periodic observations.…”
Section: Introductionmentioning
confidence: 99%
“…having no threat to infrastructure) make Hollin Hill an ideal site to trial new landslide monitoring techniques; the British Geological Survey has investigated and monitored landslides at Hollin Hill for several years (e.g. Chambers et al, 2008Chambers et al, , 2011Gunn et al, 2013;Merritt et al, 2013). Two of the lobes of slumped material were instrumented with three clusters of active waveguides (as described by Dixon et al (2014)); the instrumentation cluster locations are shown in Fig.…”
Section: The Hollin Hill Case Study Introductionmentioning
confidence: 99%